ANALISIS PENGARUH UKURAN PERUSAHAAN DAN KOMISARIS INDEPENDEN TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Wicaksono, Dimas (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This study aims to examine the influence of the company and independent commissioners on intellectual capital disclosure with profitability as a moderating variable. The dependent variable in this study is disclosure of intellectual capital. While the independent variables in this study are company size and independent commissioners, while profitability is the moderating variable. The population in this study are companies listed on the Kompas 100 Index of the Indonesia Stock Exchange for the period 2015-2019. Methods of data collection in this study using content analysis methods from 22 sample companies. To analyze the relationship between the independent variable and the dependent variable with the panel data regression analysis method. The results of this study indicate that company size has a positive effect on intellectual capital disclosure. Independent commissioners have a positive effect on intellectual capital disclosure. Profitability of the effect of company size on intellectual capital disclosure. Profitability is not able to influence the effect of independent commissioners on intellectual capital disclosure.